Ameloblastic fibro-odontoma: case report (Research, Society and Development, 2021)
The appearance of ameloblastic fibro-odontoma is uncommon, representing only 1% to 3% of odontogenic tumors. Moreover, it occurs mainly in children and young people, with more than 90% of cases in the first two decades of life, with a predilection for males. The posterior mandible region is the most affected, followed by the posterior maxilla region, in view of its asymptomatic character, FOA is usually diagnosed during routine panoramic radiographs, or when the origin of delayed eruption of teeth is investigated, histopathologically, the lesion resembles enamel or dental pulp organ, containing fragments of immature mineralized tissue, such as enamel, dentin and cementum, and the treatment of choice is conservative surgery, such as enucleation and curettage. The aim of this study is to report a case of ameloblastic fibro-odontoma (AFO) in a six-year-old patient as well as its orofacial manifestations, radiographic findings, histopathological report, differential diagnosis for proper treatment and correlate it with the literature from a narrative/critical review by accessing the major databases namely; PubMed (Medline), Web Of Science, Scopus and Lilacs using DeCS controlled vocabulary terms.